Ответ:
------------------------------------
Пошаговое объяснение:
Решение:
1)
2)
3)
Сокращение:
-----------------------------------
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
------------------------------------
Пошаговое объяснение:
Пример:
Решение:
1)![2\frac{3}{8}-1\frac{2}{3}=2\frac{9}{24}-1\frac{16}{24}=1\frac{33}{24}-1\frac{16}{24}=\frac{17}{24} 2\frac{3}{8}-1\frac{2}{3}=2\frac{9}{24}-1\frac{16}{24}=1\frac{33}{24}-1\frac{16}{24}=\frac{17}{24}](https://tex.z-dn.net/?f=2%5Cfrac%7B3%7D%7B8%7D-1%5Cfrac%7B2%7D%7B3%7D%3D2%5Cfrac%7B9%7D%7B24%7D-1%5Cfrac%7B16%7D%7B24%7D%3D1%5Cfrac%7B33%7D%7B24%7D-1%5Cfrac%7B16%7D%7B24%7D%3D%5Cfrac%7B17%7D%7B24%7D)
2)![2\frac{7}{16}-\frac{17}{24}=2\frac{21}{48}-\frac{34}{48}=1\frac{69}{48}-\frac{34}{48}=\frac{35}{48} 2\frac{7}{16}-\frac{17}{24}=2\frac{21}{48}-\frac{34}{48}=1\frac{69}{48}-\frac{34}{48}=\frac{35}{48}](https://tex.z-dn.net/?f=2%5Cfrac%7B7%7D%7B16%7D-%5Cfrac%7B17%7D%7B24%7D%3D2%5Cfrac%7B21%7D%7B48%7D-%5Cfrac%7B34%7D%7B48%7D%3D1%5Cfrac%7B69%7D%7B48%7D-%5Cfrac%7B34%7D%7B48%7D%3D%5Cfrac%7B35%7D%7B48%7D)
3)![2\frac{7}{12}+\frac{35}{48}=2\frac{28}{48}+\frac{35}{48}=\frac{63}{48} 2\frac{7}{12}+\frac{35}{48}=2\frac{28}{48}+\frac{35}{48}=\frac{63}{48}](https://tex.z-dn.net/?f=2%5Cfrac%7B7%7D%7B12%7D%2B%5Cfrac%7B35%7D%7B48%7D%3D2%5Cfrac%7B28%7D%7B48%7D%2B%5Cfrac%7B35%7D%7B48%7D%3D%5Cfrac%7B63%7D%7B48%7D)
Сокращение:
-----------------------------------
Уравнение:
УДАЧИ!